(untitled) (Research, Society and Development, 2023)
Stroke is the second leading cause of death in the world and the mortality rate in Brazil is among the highest in Latin America and, although this mortality rate has decreased in recent years, the Northeast still has high rates. The objective of this work was to study mortality from stroke in the Northeast region of Brazil between the years 2008 to 2018. To this end, an epidemiological, cross-sectional, descriptive, quantitative, time-series study was carried out, with secondary data obtained from the database of data from the Ministry of Health - DATASUS, where the ICD codes I60 to I69 were included in the research, imported from TABNET-DATASUS to the Excel program, and later exported to the Bioestat 5.3 program for statistical analysis. The data showed that stroke was responsible for 308,793 deaths in the Northeast during the study period, with ICD 10 – I64, I69, I67 and I61 being the most reported. The year with the highest number of deaths was 2015 with a peak of 29,005 cases. Predominance of deaths in males with 50.07% and in the age group of 80 years or older, with brown and married individuals being the most reported individuals with 57.0% and 35.0% of cases, respectively, and individuals aged 12 years or older. more than studies, the least affected. In view of this, it is understood the relevance of studies on this disease, and the importance of instituting preventive measures to avoid sequelae and reduce the number of deaths, which victimize countless patients affected by stroke.